Herbal Nanoparticle-Embedded Film-Forming Spray: A Novel Topical Delivery System for Vitiligo Management - Rayabagi, Madhuri H; Prajapati, Bijal (Indian Journal of Pharmaceutical Education and Research)
Objectives: This study evaluated a topical film-forming spray designed to improve the skin permeation of curcumin and piperine-loaded nanoparticles, aiming to enhance therapeutic efficacy and reduce dosing frequency for managing vitiligo. Materials and Methods: The HPMC E15, Polyethylene glycol 6000 and Eudragit RS100, blended in cold water and ethanol (50:50). Six criteria were utilized for evaluation: drying time, viscosity, appearance, skin effect, stickiness and water washability. The study selected Propylene Glycol (PG) and Polyethylene Glycol (PEG) 400 as plasticizers, with camphor and menthol to enhance penetration. A 32 Factorial design was used to optimize the formulation using Polymer concentration (X1) and Plasticizer concentration (X2), focusing on drying time and in vitro drug release. The film-forming spray was evaluated. Results and Discussion: HPMC E15, in a blend of cold water and ethanol (50:50), satisfies the rating criteria. Increase propylene glycol concentration expands the spray area and preserve elasticity. The FTIR study shows no interaction. The drug content and average weight per dose in all formulated batches range from 93.5% to 95.5% and from 0.078±0.004 g to 0.098±0.002 g, respectively. The drying time ranged from 181.2 to 258 sec. The spray pattern exhibits good uniformity and is nonspherical. Spray angle, pH and leakage test are within acceptable limits. Viscosity ranges between 10648 to 10895 cp and shows good spray ability. The weight, thickness uniformity, folding endurance and tensile strength of the film were found to be satisfactory. All formulations showed drug release range of 82.34% to 96.88%. The TEM images showed irregular, non-porous structure, while XRD confirmed an amorphous nature. Conclusion: The developed film-forming spray demonstrated favorable physicochemical properties, enhanced drug release, and stability, indicating its potential as an effective topical delivery system for vitiligo.
Keywords: Curcumin; Piperine; Desolvation Method; Nanoparticles; Film-forming Spray